Unpacking the Jury Box - Klein, Kenneth S. (1996)
This Article challenges the accusation that juries are illequipped to do justice in a complex society. The consequences of debunking the commonly believed notion of jury incompetence are twofold. First, it reveals an alternative explanation of contemporary distrust of jurors-that distrust of juries is symptomatic of a larger dynamic whereby citizens distrust any institution of democratic decision-making when the decision-makers are diverse from themselves. Second, that much of the current slate of proposed jury reforms, which are based on the false premise of juror incompetence, will harm the institution of trial-by-jury to no end